PENGARUH PENGERINGAN TERHADAP KOMPONEN VOLATIL YANG TERLIBAT PADA EKSTRAKSI ANDALIMAN (Zanthoxylum acanthopodium DC) (Effect of Dehydration of Fruit on Volatile Aroma Constituents of Andaliman Zanthoxylum acanthopodium DC) - Meutia, Yuliasri Ramadhani; Wardayanie, Ning Ima Arie (Baristand Industri Banda Aceh, 2015)
Andaliman (Zanthoxylum acanthopodium) is typical of North Sumatra spice plant that iswidely used as specific flavor. In other hand andaliman has several benefits such as antimicrobial,antioxidant and as an immunomodulator. Studies on the effect of the extraction of the flavor componentsor potent odorant of andaliman has been done, but the effect of dehydration of the fruit before theextraction to the flavor components have not reported yet. This research were conducted to study theeffect of dehydration of the andalimanâs fruit against theirs volatile compounds. Andaliman used as rawmaterials in the study were given pretreatment by drying and then extracted by maceration method usingethanol and ethyl acetate (1 : 1) for 2 hours, 4 hours, and 6 hours. The extracts were analyzed using GCMSfollowed by GC-O to analyze potential odorants. The results showed that geranyl acetate were themain compound of both andaliman extract with dehydration of the fruit and also andaliman extractedfrom its fresh fruit. Maceration process after 6 hours can bring a new dominant flavor compoundsnamely D-Limonene besides geranyl acetate on both the treatment of the raw material. However aromawere described from sniffing port of GC-O on wet andaliman vary from andaliman-like, sour, green andflowery. While the green aroma were mostly described on dehydrated andalimanâs fruit extract. This mayconclude that the process of drying of raw materials could affect aroma that described by using GC-O.